Pengembangan Express Feeder pada Penyulang CLDG Tasikmalaya dengan Metode Particle Swarm Optimization untuk Mengurangi Rugi Daya - Maulana, Bani; Busaeri, Nundang; Risnandar, Muhammad Aris (Fuse-teknik Elektro, 2025)
The electrical power distribution system plays a crucial role in delivering reliable and efficient energy to consumers. One of the main challenges in its operation is the high level of power losses that occur during the distribution process. To address this issue, this study applies a network reconfiguration method by adding an express feeder to the CLDG Tasikmalaya feeder to reduce power losses. The optimization method used is Particle Swarm Optimization (PSO), an algorithm inspired by the social behavior of bird or fish swarms in finding the best solution. Each particle searches for an optimal position (Pbest), and others follow the global best solution (Gbest). Power flow analysis is performed using the Backward Forward Sweep (BFS) method, implemented in MATLAB 2024a and validated with ETAP 19.0.1. The BFS method constructs BIBC and BCBV matrices based on network topology. As a result, power losses were reduced from 450.485 kW to 245.1011 kW after reconfiguration.